Influência de fungos micorrízicos arbusculares sobre o desenvolvimento de berinjela infestada com Meloidogyne incognita, cultivada em substrato com pó de casca de coco - Oliveira, Elimário Teixeira de (2015)
The eggplant (Solanum melongena L.) belongs to the Solanaceae family, is cultivated for commercial purposes and its way of spreading is through seeds and seedlings. To ensure good productivity, it is also necessary to use suitable substrates and plants resistant to the attack of phytopathogens, especially nematodes such as Meloidogyne incognita. In this regard, the use of dried coconut shell powder has been tested in the composition of substrate to produce seedlings. Studies also show that the association eggplant-nematode-arbuscular mycorrhizal fungi (AMF) is very peculiar and mechanical damages caused by nematodes have been reduced in plants colonized by these fungi. This study aimed to evaluate the influence of mycorrhizal symbiotic association on the development of eggplant grown in different proportions of substrate containing powder of dried coconut shell under the infestation of M. incognita. The experiment was conducted in a greenhouse. The experimental design was completely randomized, comprising 12 treatments and 6 replicates in the following combinations: T1 100% soil + AMF; T2 100% soil; T3 100% soil + nematodes; T4 100% dried coconut shell powder + nematodes; T5 90% soil + 10% dried coconut shell powder + AMF + nematodes; T6 80% soil + 20% dried coconut shell powder + AMF + nematodes; T7 70% soil + 30% dried coconut shell powder + AMF + nematodes; T8 60% soil + 40% dried coconut shell powder + AMF + nematodes; T9 90% soil + 10% dried coconut shell powder - AMF - nematodes; T10 80% soil + 20% dried coconut shell powder - AMF - nematodes; T11 70% soil + 30% dried coconut shell powder - AMF - nematodes; T12 60% soil + 40% dried coconut shell powder - AMF - nematodes. The soil used in the substrate mixture was a Latosolic Tb Eutrophic Cambisol. The plants were inoculated with a mixture of three species of AMF (Acaulospora scrobilucata, Entrosphora colombiana and Scutelospora heterograma) obtained from the Mycorrhizal Fungi Inoculant Bank of the Sector for Soil Microbiology of the Soil Science Department of the Federal University of Ceará . The experiment was conducted for 75 days and, at the end, the following analyses were carried out: shoot fresh matter, shoot dry matter, shoot NPK contents, arbuscular mycorrhizal colonization, number of galls, egg mass, and reproduction factor. From the results we can conclude From the results we can conclude that the M. incognita infected eggplant plants grown on the substrates with 10% coconut shell powder presented the highest number of leaves; The substrates formed with the addition of 40% coconut husk powder restricted the development of eggplant plants; The N, P and K levels observed in the aerial part of eggplant were lower than the values considered adequate for the culture; The infectivity of M. incognita was reduced in plants that received the FMA inoculum with up to 20% coconut husk powder and that the use of 100% coconut husk powder compromised eggplant growth.